The Effectiveness of Flipped Classroom on the Academic Achievement of University Undergraduates - Thouqan Saleem Masadeh (International Journal of Pedagogy and Teacher Education, 2021)
The present study aimed to investigate the effectiveness of Flipped Classroom in developing the achievement of university undergraduates. The quasi-experimental approach was used and three achievement posttests were carried out. Participants were (32) students who were in advance distributed to two groups, control and experimental. Analysis of Students' achievement grades revealed that the effectiveness of Flipped Classroom use, as a learning method needs time to take place in students' academic achievement and understanding of the learning materials because of  the nature of the Flipped Classroom that flipped the whole learning process. Thus, students needed time to be familiar with this new learning method for them. Results showed that there was no significant difference between participants' achievement mean scores in the first posttest at the end of the fifth week due to the use of the Flipped Classroom or the ordinary methods. However, there was a significant difference between students' achievement mean scores in the second posttest in favor of the experimental group students who learnt the course content through the use of  Flipped Classroom. In addition, there was a significant difference in student participants' mean scores in the third posttest in favor of  the experimental group students, too. In light of these findings, it was concluded that the instructor and his students should be patient for some time for the effectiveness of using the Flipped Classroom learning method to be noticed. Moreover, considerable time should be spent on familiarizing students with this new learning method.